Extractive industries and regional diversification: A multidimensional framework for diversification in mining regions. (September 2022) - Breul, Moritz; Atienza, Miguel
Highlights: Need for a subnational framework to understand diversification in mining regions. Article proposes multidimensional framework (regional, multi-scalar, temporal). Effect of extractive industries on regional diversification is mediated by these dimensions. Reveals potential for cross-fertilization between research on the relationship between resource extraction and development and research on regional diversification in economic geography. Abstract: Economic diversification is seen as imperative for mining regions to achieve an economically sustainable form of development. Yet, existing knowledge is largely drawn from national scale analyses, thereby concealing interregional differences as well as mechanisms between resource extraction and diversification operating at the regional scale. This special issue on 'Extractive Industries and Regional Diversification' therefore shows recent work that brings the study of the relationship between extractive industries and diversification to a regional level. In this introductory article, we propose a multidimensional framework that seeks to refine our understanding of mining regions' (in)ability to diversify their economies by bringing together insights from research on the relationship between resource extraction and development and research on regional diversification in economic geography. We argue that the effect of extractive industries on regional diversification is mediated along three dimensions, that is (1) the regional context conditions, (2) the multi-scalar organization of extractive industries, and (3) the relevance of temporality. The framework is applied to synthesize the key insights of the special issue articles and directions for future research are derived.